Identification of Spongionella compounds as cyclosporine A mimics. (May 2016) - Sánchez, Jon Andoni; Alfonso, Amparo; Leirós, Marta; Alonso, Eva; Rateb, Mostafa E.; Jaspars, Marcel; Houssen, Wael E.; Ebel, Rainer; Tabudravu, J.; Botana, Luís M.
Graphical abstract: Abstract: Marine sponges are found to be a wide source of bioactive compounds with different effects such as anti-inflammatory or anticancer actions among others. Cyclophilin A (Cyp A) is a target protein implicated in the mechanism of action of immunosuppressive compounds such as Cyclosporine A (CsA). In the present paper we studied the binding between 4 Spongionella compounds (Gracilins H, A, L and Tetrahydroaplysulphurin-1) and Cyp A immobilized over a CM5 sensor chip. Thus, we found that Spongionella compounds showed to have similar binding affinities than CsA with dissociation equilibrium constant in the range. Next, the effect of these Spongionella isolated compounds was tested over calcineurin phosphatase activity. The same than CsA, Gracilin H, A and Tetrahydroaplysulphurin-1 were able to inhibit phosphatase activity once the complex between Cyp A-CsA/ Spongionella compounds was formed. The ability to avoid the dephosphorylation of NFATc1 was also checked in human T cells isolated from peripheral blood. First, cells were pre-treated with Spongionella compounds or CsA following by Concanavalin A (Con A) stimulation. In these conditions nuclear NFATc1 levels were diminished either by CsA or Gracilin A, L, and Tetrahydroaplysulphurin-1 treatment. Moreover, as happens with CsA due to the inhibition of NFATc1, Interleukine-2 (IL-2) released to the culture medium was significantly decreased with all Spongionella compounds. Results conclude that, Spongionella derivatives preserve T lymphocytes from activation modulating the same pathway than CsA. Thus, this mechanism of action suggests that these compounds could be interesting candidates in drug development as immunosuppressive or anti-inflammatory drugs.